1944
DOI: 10.1063/1.1723938
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Chain Copolymerization Reactions

Abstract: The kinetics of chain copolymerizations is developed for reactions consisting of three steps: first, an activation of stable monomer; second, a growth of activated polymer radical by means of monomer addition; third, a stabilization of the growing chains by (a) monomer addition, (b) by means of growing polymer [Eq. (1)]. The existence of a steady state in respect to the concentration of growing chains beyond the induction period is assumed. The rate constants of growth and termination will in general depend up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

1948
1948
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(49 citation statements)
references
References 17 publications
0
49
0
Order By: Relevance
“…Assuming that the effect of side reactions on the yield of a given monomer remains constant in going from simple polymer to copolymers, and that the C-C bonds in the vinyl chain and sequences are of equal strength for a given monomer, then the pyrolysis yield of monomer from the copolymer formed at low conversion can be calculated if one lmows the yield from the simple polymer, the monomer reactivity ratios (r A and rB) [11,12], and the composition of the monomer charge. The probability of regenerating monomer A, for example, styrene, from the simple polymer can be considered unity.…”
mentioning
confidence: 99%
“…Assuming that the effect of side reactions on the yield of a given monomer remains constant in going from simple polymer to copolymers, and that the C-C bonds in the vinyl chain and sequences are of equal strength for a given monomer, then the pyrolysis yield of monomer from the copolymer formed at low conversion can be calculated if one lmows the yield from the simple polymer, the monomer reactivity ratios (r A and rB) [11,12], and the composition of the monomer charge. The probability of regenerating monomer A, for example, styrene, from the simple polymer can be considered unity.…”
mentioning
confidence: 99%
“…This will also lead us to relations between surface and bulk properties. It is worthwhile to mention that Simha contributed to understanding random copolymers not only with the equation of state but also with the pioneering paper on kinetics of copolymerization [Simha and Branson, 1944].…”
Section: Preliminariesmentioning
confidence: 99%
“…Using the assumption that the rate of monomer addition to a radical chain depends only on the nature of the last unit on the chain, Dostal, [1] in 1936, showed that only four propagation reactions and corresponding rates would describe copolymerization of two monomers: In 1944, a useful copolymer composition relationship was derived independently by Alfrey, [2] Mayo, [3] Simha, [4] and Wall, [5] by making the further assumption that steady state applies to each radical type separately. Composition relationships for dipolymers were derived by early workers in the polymer field.…”
Section: � Copolymer Composition Relationshipsmentioning
confidence: 99%
“…4 An overall radical generation rate at 100% efficiency ρ is used, and an overall polymerization rate coefficient k p for the particular copolymer composition and reaction temperature.…”
Section: � Emulsion Polymerization Kineticsmentioning
confidence: 99%